THE INFLUENCE OF TAX UNDERSTANDING, TAXPAYER AWARENESS, QUALITY OF SERVICE AND TAX SANCTIONS ON COMPLIANCE OF TAXPAYERS AT KPP PRINCIPAL MEDAN PETISAH - Gembira Marbun; Rolia Rumabutar (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
This research aims to determine the influence of understanding taxation, taxpayer awareness, service quality, and tax sanctions on MSME taxpayer compliance at KPP Pratama Medan Petisah. The data collection technique in this research uses a questionnaire in the form of a Likert scale. Respondents in this study were taxpayers registered at KPP Pratama Medan Petisah. The number of taxpayers in the sample in this study was 100 respondents. The sample method used in this research was simple random sampling. The analysis technique used is a multiple linear analysis technique. The research results show that understanding taxation has a significant positive effect on taxpayer compliance MSME, taxpayer awareness has a significant positive effect on taxpayer compliance MSME, service quality has a significant positive effect on taxpayer compliance MSME, and tax sanctions have a significant positive effect on unpaid compliance MSME.